Influence of Fadama I Project on the Socio-Economic Status of Farmers in Kebbi and Sokoto States, Nigeria - Lawal, N. I.; Okeh, B.I.; Uguru, C. (American Journal of Education and Learning, 2016)
Fadama I project in Nigeria has attracted assistance (Funds) from the World Bank. Kebbi and Sokoto states are two of the beneficiaries of the funds. Participating in the project is an important aspect that could assist the funding institution measure progress, determine improvement and design developmental programme. This study therefore, determines the impact of fadama I project on participants’ socio economic status in Kebbi and Sokoto state, Nigeria. Specific objectives includes: Describe the personal characteristics of fadama I users; to assess the area of respondent’s involvement in fadama I project; to analyze the benefit derived by participating in the fadama I project; to determine the problem faced by the participants in the fadama I project. A multi stage random sampling procedure was used to select 400 respondents from the communities participating in Fadama I project. Questionnaire distribution was used to elicit information from the respondents. Descriptive statistics such as frequency counts, percentages were used for data analysis while Regression Analysis was the inferential statistics used. R2 value of 0.237 and the R value of 0.71 are all positive. This shows that Fadama I project has influenced socio economic status of the participants’. The study therefore concluded that the impact of Fadama I project on the socioeconomic status of the participant is Positive. It therefore, recommended that Development Agency needs to motivate Farmers to participate in Fadama II, III and its extension projects by providing more assistance (funds) to the states involved.